Book Review of Jennifer Wemigwans (2018). A Digital Bundle: Protecting and Promoting Indigenous Knowledge Online. Regina, SK: University of Regina Press. - Shezadi Khushal (Canadian Society for Studies in Education, 2022)
This paper is a review of author Jennifer Wemigwans' book, A Digital Bundle: Protecting and Promoting Indigenous Knowledge Online. It investigates a critical issue in education and highlights the relationship between Indigenous Peoples and the internet, the flow of communication, protection, and access to Indigenous Knowledge online, and the safeguarding of freedom of expression of Indigenous Knowledge online. It makes a correlation between the protection of digital technology to that of Indigenous self-determination, resurgence, and revitalization. By embracing Indigenous theories and methodologies, this book heightens Indigenous voices, providing tools for empowerment.